Management of Early Childhood Caries under General Anesthesia at a Tertiary Care Service Hospital: A Retrospective Study - Anoop Sharma; Aditi Jain; M. M. Dempsy Chengappa; Nikhil Kumar Meshtha; H. K. Goje (Journal of Marine Medical Society)
Introduction: Early childhood caries (ECC) affects almost 50% of preschool children and may lead to chronic pain, halitosis, fever, trismus, poor growth and development, and repeated airway and gastrointestinal infections. Managing this is challenging in the face of anxiety, developmental delay, and other comorbidities in children. This necessitates their management under general anesthesia (GA). Methodology: We carried out a retrospective descriptive study to analyze the characteristics of pediatric patients who underwent oral rehabilitation under GA at a tertiary care service hospital. Results: The data of 20 children inflicted with ECC who underwent full-mouth rehabilitation under GA were analyzed. The majority were boys and the mean age was 69.5 months. Five of these children had comorbidities. The most common indication for GA was the uncooperation of the child. Inhalational induction was carried out for most of them, and postoperatively, two children had emergence delirium and one child had nausea and vomiting. Conclusion: We share our experiences toward standardization of safe anesthesia practices.